2020
DOI: 10.1038/s41416-020-01134-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelets enhance malignant behaviours of gastric cancer cells via direct contacts

Abstract: In this study, we aimed to analyse human cancer cell–platelet interactions in functional cell analyses and explore the molecular mechanisms behind tumour progression. Various functional analyses of gastric cancer (GC) cells were performed after direct/indirect co-incubation with platelets derived from GC patients. Further detailed expression and signalling analyses were performed after co-culture with direct and indirect GC cells–platelet contact. Malignant behaviours of cancer cells, such as proliferation, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Another more recent study demonstrated that direct contact between platelets isolated from patients with advanced gastric cancer and gastric cancer tumor cells induced processes of migration, invasion, adhesion, and expression of MMP9 in tumor cells [217]. Extravasated platelet aggregates have been evidenced in invasive parts of clinical samples from human pancreatic cancer biopsies.…”
Section: Contribution Of Platelets To Cancer Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Another more recent study demonstrated that direct contact between platelets isolated from patients with advanced gastric cancer and gastric cancer tumor cells induced processes of migration, invasion, adhesion, and expression of MMP9 in tumor cells [217]. Extravasated platelet aggregates have been evidenced in invasive parts of clinical samples from human pancreatic cancer biopsies.…”
Section: Contribution Of Platelets To Cancer Developmentmentioning
confidence: 99%
“…These aggregates are associated with markers for the first steps of EMT, such as increased expression of Snail1 and reduced E-cadherin. Ishikawa et al reported that in 60% of the samples from a Japanese cohort of patients with HER2 negative breast cancer (biopsy samples), platelets were found directly surrounding the primary tumor cells, and that these tumor cells showed the expression of EMT markers [217].…”
Section: Contribution Of Platelets To Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts indicate that tumor cells in the first phase of metastasis depend on at least two signals from platelets (through direct and indirect tumor/platelet contact), whereby signal transmission through platelet-cell contact is mandatory for metastasis formation. Accordingly, a recent study has shown that direct contact between platelets isolated from advanced gastric cancer patients and gastric cancer cells particularly induced migration, invasion, adhesion, and MMP9 expression in the tumor cells (54).…”
Section: Invasion Of the Basement Membrane And Cell Migrationmentioning
confidence: 99%
“…Cancer metastasis consists of an invasion-metastasis cascade, namely, tumor cells firstly exit their primary growth sites, survive in the circulation, extravasate at distant organ site, and lastly proliferate in the foreign microenvironments ( 144 ). Tumor cell-educated platelet (TEPs) participated in multiple steps of metastasis, helping the “villain” to do evil ( 134 , 145 ). Blocking platelet activation ( 146 ) or in the absence of platelets ( 147 ), cancer metastasis was markedly repressed.…”
Section: Platelet–supported Cancer Progressionmentioning
confidence: 99%